Ultra Petita Dalam Tindak Pidana Pemerkosaan - Chanifah Chanifah; Elly Sudarti; Nys. Arfa (Fakultas Hukum, Universitas Jambi, 2023)
In the criminal realm there are no provisions that explicitly state the permissibility or inability of judges to decide beyond what is required. Where this indirectly becomes the limit of the judge in deciding the case. The panel of judges can pass a lower, equal or even higher decision than the public prosecutor's requisitor. Judges have freedom and independence in deciding cases, in this case it can be found in the trial facts that the thing that weighs on the defendant is that when the Panel of Judges is convinced that a sentence is higher than the demands of the Public Prosecutor, then in fact the sentence does not violate the criminal procedure law. So according to the author, the Ultra Petita decision of the panel of judges is in line with the provisions of laws and regulations because it does not at all go beyond the maximum legal limits set out in Article 285 of the Criminal Code. Abstrak Dalam ranah pidana tidak ada ketentuan yang menyatakan secara eksplisit mengenai kebolehan atau ketidakbolehan hakim dalam memutuskan melebihi apa yang diminta. Dimana hal tersebut secara tidak langsung menjadi batasan hakim dalam memutus perkara. Majelis hakim dapat menjatuhkan putusan lebih rendah, sama atau bahkan lebih tinggi dari rekuisitor penuntut umum. Hakim memiliki kebebasan dan indepedensi dalam memutus perkara, dalam kasus ini dapat ditemukan dalam fakta persidangan bahwa hal yang memberatkan terdakwa adalah ketika Majelis Hakim berkeyakinan untuk menjatuhkan pidana lebih tinggi dari tuntutan Jaksa Penuntut Umum, maka sebenarnya hukuman itu tidak melanggar hukum acara pidana. Sehingga menurut penulis, putusan Ultra Petita majelis hakim telah sejalan dengan ketentuan peraturan perundang-undangan karena sama sekali tidak keluar dari batasan maksimal hukum yang telah ditetapkan dalam Pasal 285 KUHP.